A method to selectively internalise submicrometer boron carbide particles into cancer cells using surface transferrin conjugation for developing a new boron neutron capture therapy agent. Issue 1 (1st January 2020) - Tsuji, Takuma; Yoshitomi, Hiroshi; Ishikawa, Yoshie; Koshizaki, Naoto; Suzuki, Motoshi; Usukura, Jiro
Abstract: With the goal of developing a new type of boron neutron capture therapy (BNCT) agent, selective internalisation of submicrometer boron carbide spherical particles into cancer cells via surface transferrin conjugation is demonstrated and confirmed in vitro and in vivo . Herein, negatively charged, spherical, submicrometer boron carbide (B4 C) particles were coated with positively charged poly-L-lysine and negatively charged poly-γ-glutamic acid; the particles were subsequently conjugated with transferrin. It was confirmed in vitro and in vivo by confocal laser scanning microscopy and transmission electron microscopy that the coated particles interacted with transferrin receptors that were highly expressed on the surface of cancer cells, endocytosed by tumour cells, and transferred to the proximity of the nucleus. The submicrometer size of the particles provided stronger interaction between transferrin and transferrin receptors and hence resulted in more efficient internalisation than that obtained using nanoparticles. This method might be effective for the selective internalisation of large submicrometer particles for high therapeutic effects due to the large particle size, but with small particle dosages.